Overview of Basic Immunization Coverage in Infants During the Covid-19 Pandemic in North Sumatra - derani, Derani; Lubis, Alvi Hazri; Harahap, Mina Ainun; Aljutri, Aljutri; Susanti, Nofi (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
Immunization is a health program that aims to increase immunity or avoid a disease. Around 800 thousand children in the whole of Indonesia risky tall to diseases That can prevented with vaccines ie tetanus, diphtheria, measles, rubella, as well as polio due to the COVID-19 pandemic in Indonesia. This research uses descriptive methods and this research uses secondary data obtained from the North Province Health Office. During the Covid-19 pandemic, immunization coverage was obtained, namely in 2020 infants who had received complete immunization, namely 221937 infants while those who received incomplete immunization were 70953 infants. Furthermore, in 2021 those who have received complete immunization are 215919 babies while those who have received incomplete immunization are 51617 babies. In 2022 those who have received complete immunization are 243320 babies while those who have received incomplete immunization are 23675 babies. Infants aged 0 - 1 1 month in North Sumatra Province have not all been fully immunized due to the side effects of the Covid-19 pandemic.